1994
DOI: 10.1210/jcem.79.2.8045953
|View full text |Cite
|
Sign up to set email alerts
|

The combined corticotropin-releasing hormone/lysine vasopressin test discloses a corticotroph phenotype.

Abstract: The combined administration of CRH and vasopressin to man now offers a powerful means to directly assess the pituitary corticotroph reserve. A double blind, randomized, placebo-controlled, cross-over trial offered the opportunity to perform the combined CRH/lysine vasopressin (LVP) test (100 micrograms ovine CRH, followed by 1 IU LVP over 15 min) on 3 different occasions without treatment in 10 normal male subjects. We showed that peak ACTH plasma levels after stimulation had wide intersubject variation, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Genetic or acquired individual characteristics could explain the variable HPA tone (Bertagna et al, 1994;Huizenga et al, 1998a). On the other hand, a difference in cortisol metabolism could be involved because the plasma metabolic clearance (MCR) of cortisol is increased in obese subjects (Strain et al, 1980(Strain et al, , 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic or acquired individual characteristics could explain the variable HPA tone (Bertagna et al, 1994;Huizenga et al, 1998a). On the other hand, a difference in cortisol metabolism could be involved because the plasma metabolic clearance (MCR) of cortisol is increased in obese subjects (Strain et al, 1980(Strain et al, , 1982.…”
Section: Discussionmentioning
confidence: 99%
“…This probably indicates the need to extend such studies to larger groups of individuals, including healthy overweight and obese subjects to investigate all characteristics of low-responsive vs. high-responsive subjects. It should not, in fact, be forgotten that the HPA axis response to CRH plus lysine vasopressin (24) and ACTH (25) stimulation also varies markedly from one individual to the next in relation to various factors, including genetic background (24), time of day (25), and possibly other unidentified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have reported only the central effects of centrally administered CRH or the stim ulation of the pituitary corticotrope cells -outside the blood-brain barrier (BBB) -after the peripheral adminis tration of CRH [3,4,[10][11][12][13]. Few papers deal with the possible central effects of peripherally administered CRH or the peripheral effects of centrally administered CRH.…”
Section: Introductionmentioning
confidence: 99%